Temperature Discrepancy and its Relation to the Most Important Physiological (Hormonal) Variants According to Teaching Climate in Handball Lesson - Nazar Hussein al-Naffakh (Journal of Global Pharma Technology, 2017)
The study includes several aspects focused on the importance of identifying hormones levels in the blood of (female) students according to the climate of teaching at different temperatures and recognizing the dysfunction of students. The method was through dividing the samples into three groups each group contains six students and the blood sample is withdrawn before, during, and after the lesson, each group within a certain climatic period, divided into a moderate period, a cold period, and a hot period, where the specialist took blood samples from students at different temperatures in the environment of teaching handball. The first period of the climate is the moderate period where the specialist took blood samples and examined them in vitro. The results were recorded. In the second period, the cold weather, blood samples were also taken from the students. They were examined and the results were obtained. Finally, the hot period, the specialist also drew blood from the students, examined them and obtained the results. After finalizing the field work, the results of the three groups were collected and statistically compared.Keyword: Temperature Discrepancy, Physiological, Teaching Climate and Handball Lesson.